Enhancement the Competitiveness of Serang MSME’s Through Legality Analysis of The Role of Public Policy - Hamdan Hamdan; Deviyantoro Deviyantoro (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Licensing is one of the main things that must be owned by people who want to establish MSMEs in Indonesia. There are several types of licensing that must be taken according to the type of MSME you want to establish. More and more detailed permits are usually owned by food and cosmetic MSMEs because they are directly related to consumer health. Meanwhile, for small and medium enterprises (SMEs) permits can only be issued by districts or cities and must submit a Taxpayer Identification Number (NPWP). It is hoped that this regulation will provide the business community with protection, legal certainty, assistance, and ease of access to financing through banking and non-banks. Since 2018, the implementation of the Online Single Submission System (OSS) still often encounters various obstacles, for example from the number of business actors who come to apply for permits, not all of them have completed obtaining business and commercial permits. Some who register only get a Business Identification Number (NIB), a study on the role of legality on the competitiveness of MSME’s  and the policies that support it are very important to do, especially in cities or districts that still lack knowledge of these problems, for this reason this research was carried out by taking 30 saturated samples from the agribusiness SME community in the city of Serang, Banten province. Quantitative analysis was performed using the PLS method. The results show that legibility does have an effect on increasing the competitiveness of SMEs by 34.07%.